Voting about God in early church councils - MacMullen, Ramsay, 1928-2022. (London: Yale University Press, 2006)
"What was it like to be a bishop in the early church voting on what God's law should be? How did bishops who disagreed about God's law conduct themselves? Often they were raucous, riotous, even violent in settling disputes. Ramsay MacMullen steps aside from the well-worn path that previous scholars have trod to explore exactly how early Christian doctrines became official. Drawing on extensive verbatim stenographic records, he analyzes the ecumenical councils from A.D. 325 to 553, in which participants gave authority to doctrinal choices by majority vote."--Jacket.
Introduction -- The democratic element -- The cognitive element -- The 'supernaturalist' element -- The violent element -- Preliminaries -- Councils in action -- The stage -- Dioscorus -- Management -- Exact words.
Includes bibliographical references (pages 155-166) and index.
Keywords: Councils and synods; Church history -- Primitive and early church, ca. 30-600.; God (Christianity) -- History of doctrines -- Early church, ca. 30-600.